Program Penguatan Pembelajaran Bahasa Asing di SMA Melalui Kolaborasi dengan Masyarakat - Dalle, Ambo; Amir, Johar; Fatimah Al Ilmullah, Syarifah; Mannahali, Misnah; Angreany, Femmy (Jurusan Pendidikan Teknik Elektro, 2025)
This program explores the implementation of a community-collaborative program to enhance foreign language learning at the senior high school level. Recognizing the limitations of classroom-based, theory-oriented instruction, the research addresses the need for contextual and experiential approaches. The program aimed to bridge formal education and real-world language use by involving local communities in the learning process. Using a collaborative action research design, the study engaged teachers, students, and community partners including language practitioners and native speakers in four iterative stages: planning, action, observation, and reflection. Data were collected through pre- and post-tests, interviews, observations, and reflective journals. Findings indicate a substantial improvement in students’ foreign language proficiency, with an average score increase of over 20% across speaking, listening, reading, and writing skills. Moreover, students demonstrated enhanced motivation, confidence, and communicative competence. Community involvement provided authentic linguistic environments, enabling students to apply language skills meaningfully in real-life contexts. The study concludes that community-based collaboration not only improves academic outcomes but also fosters character development aligned with 21st-century learning goals and Indonesia’s Profile of Pancasila Students. It recommends integrating community partnerships as a core component of sustainable foreign language education in schools.